E-Cadherin repression increases amount of cancer stem cells in human A549 lung adenocarcinoma and stimulates tumor growth. Issue 8 (17th April 2016) - Farmakovskaya, M.; Khromova, N.; Rybko, V.; Dugina, V.; Kopnin, B.; Kopnin, P.
ABSTRACT: Here we show that cancer stem cells amount in human lung adenocarcinoma cell line A549 depends on E-cadherin expression. In fact, downregulation of E-cadherin expression enhanced expression of pluripotent genes (c- MYC, NESTIN, OCT3/4 and SOX2 ) and enriched cell population with the cells possessing the properties of so-called 'cancer stem cells' via activation of Wnt/β-catenin signaling. Repression of E-cadherin also stimulated cell proliferation and migration in vitro, decreased cell amount essential for xenografts formation in nude mice, increased tumors vascularization and growth. On the other hand, E-cadherin upregulation caused opposite effects i.e. diminished the number of cancer stem cells, decreased xenograft vascularization and decelerated tumor growth. Therefore, agents restoring E-cadherin expression may be useful in anticancer therapy.